RESPONDER: Observations of a supraglacial lake drainage event at Lake 028 on Store Glacier, Greenland, July 2018 - Chudley, Thomas; Doyle, Samuel; Schoonman, Charlotte; Bougamont, Marion (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2019)
Datasets from the Resolving subglacial properties, hydrological networks and dynamic evolution of ice flow on the Greenland Ice Sheet (RESPONDER) project as published in the paper by Chudley et al. entitled "Supraglacial lake drainage at a fast-flowing Greenlandic outlet glacier". Please cite this paper if using this data. This dataset consists of observations of the rapid drainage of a supraglacial lake on Store Glacier, a marine-terminating outlet glacier of the west Greenland Ice Sheet. 'Lake 028', located 70.57degN, 50.08degW, drained on 2018-07-07 and was recorded using a variety of geophysical instrumentation. The dataset presented here includes all data necessary to replicate the findings presented in the main paper, including UAV photogrammetry-derived raster data (producing a series of orthophotos, digital elevation models, and velocity fields) and time-series records from in-situ geophysical instrumentation (GPS receiver, geophone, and water pressure sensor). Funding was provided by NERC DTP grant NE/L002507/1 and ERC Horizon 2020 grant 683043. : By the 2018-07-07 lake drainage event, Lake 028 was instrumented with a GPS receiver, seismometer, and pressure transducer sensor. A dual-frequency GPS was installed ~600 m upstream of the lake in July 2017, and by July 2018 had advected into a position immediately south of the lake. A seismometer was installed in May 2018, and a water-level sensor on 2018-07-04. From this date, regular UAV surveys (See SI Appendix, Table S1 in associated publication) were performed over the lake and surrounding environments. A detailed description of the data collection, quality control, processing and analysis is given in: Chudley, T.R., Christoffersen, P., Doyle, S. H., Bougamont, M., Schoonman, C. M., Hubbard, B., and James, M. (2019) Supraglacial lake drainage at a fast-flowing Greenlandic outlet glacier. In press. : UAV: Custom-built Skywalker X8 fixed-wing UAV running ArduPlane autopilot software, collecting imagery with a Sony α6000 and GPS data with an Emlid Reach receiver. Images processed in Agisoft Metashape v 1.4.3. Pressure Transducer: Solinst 3001 Levelogger GPS: Trimble NetR7 GPS with Trimble Zephyr Geodetic III Antenna Seismometer: HG-7 geophone recorded to a DiGOS DATA-CUBE : GPS data have been filtered with a two-pole, low-pass Butterworth filter with a 30-minute cutoff period. This 30-minute window was chosen based on a worst-case horizontal positional uncertainty of 0.035 m and a base ice velocity of ~650 m a-1, following from which assumptions the period over which velocities can be resolved is ~0.5 hours. Uncertainty was calculated based on a conservative estimate of the positional uncertainty of ±1 cm propagated through the velocity calculation. Seismometer data were decimated to 100 sps and a 2-pole, zero-phase bandpass filter (10-50 Hz) was applied to eliminate instrument and high-frequency noise. We assign UAV-derived orthophoto and DEM data uncertainties of ±0.12 m horizontally (~1.1x the ground sampling distance) and ±0.14 m vertically (~1.3x the ground sampling distance), following Chudley et al. (Cryosphere, 13, 955-968, 2019). Uncertainties in the velocity field were calculated based upon a displacement uncertainty of 0.17 m. A detailed description of the data collection, quality control, processing and analysis is given in: Chudley, T.R., Christoffersen, P., Doyle, S. H., Bougamont, M., Schoonman, C. M., Hubbard, B., and James, M. (2019) Supraglacial lake drainage at a fast-flowing Greenlandic outlet glacier. In press.